2018
DOI: 10.1155/2018/6916920
|View full text |Cite
|
Sign up to set email alerts
|

A CFA-Induced Model of Inflammatory Skin Disease in Miniature Swine

Abstract: Similarities between porcine and human skin make the pig an ideal model for preclinical studies of cutaneous inflammation and wound healing. Complete Freund's adjuvant (CFA) has been used to induce inflammation and to study inflammatory pain in several animal models. Here, we evaluated the inflammation caused by CFA injected in different layers of skin and subcutaneous (SC) tissue in a large-animal model. The degree of inflammation was evaluated at early and late time points by visual inspection and histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We finally carried out intraplantar injection of CFA to determine whether γδT cells contribute to chronic inflammatory pain, an example of granulomatous inflammation that does not resolve ( 44 ). Similar to the formalin and incisional wound models, no significant effects were observed in male ( n = 9–12) or female ( n = 6–9) littermates when assessed for mechanical ( P ≥ 0.226, two-way RM-ANOVA) and thermal ( P ≥ 0.857, two-way RM-ANOVA) hypersensitivity over 7 days ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We finally carried out intraplantar injection of CFA to determine whether γδT cells contribute to chronic inflammatory pain, an example of granulomatous inflammation that does not resolve ( 44 ). Similar to the formalin and incisional wound models, no significant effects were observed in male ( n = 9–12) or female ( n = 6–9) littermates when assessed for mechanical ( P ≥ 0.226, two-way RM-ANOVA) and thermal ( P ≥ 0.857, two-way RM-ANOVA) hypersensitivity over 7 days ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…CFA consist of mineral oil, containing a suspension of whole or pulverized heat-killed mycobacteria and its adjuvant activity results from the sustained release of antigens from the oily deposit and stimulation of a local innate immune response causing a delayed hyper-sensitivity reaction with an intense inflammatory reaction at the side of injection. 13 A previous study showed that sub-plantar injection of CFA resulted in a significant elevation in IL-1B as a proinflammatory cytokine. 20 The paw edema thickness of treatment group (Kp1, Kp2, Kp3) when compared to normal group (Kn) still have big difference in value (figure 1) because subcutaneous injection of CFA induced inflammation is still in the acute phase (0-10 days) is caused by various mediators such as histamine, serotonin, kinins and prostaglandins, released by leukocytes that migrate to the affected region and provoked a vasculo-exsudatif phenomena responsible edema.…”
Section: Figure 1 Hind Paw Edema Of Wistar Rats After 24 Hours Cfa Imentioning
confidence: 98%
“…Role of CFA is concluded that adjuvant activity from sustain release of antigens from the oily deposit and stimulation of local innate immune response causing delayed hypersensitivity reaction that can react with intense inflammatory reaction and hyperalgesia at the site of injection. 13 Therefore, this study aimed to prove the potency of bay leaves extract to prevent the inflammation, which is indicated by decreasing the paw edema thickness in rats induced with CFA.…”
Section: Introductionmentioning
confidence: 99%
“…or S.C. injection. Complete Freund’s adjuvant (CFA) is a mineral oil containing heat-killed mycobacteria that are incapable of causing disease in animals ( Navarro-Alvarez et al, 2018 ). Intraplantar injection of CFA evokes an inflammatory pain response at the site of injection, resulting in paw swelling and tactile allodynia in behavioral testing which is reduced following GlyT inhibitor administration ( Ferreira et al, 2001 ; Kassuya et al, 2003 ; Morita et al, 2008 ; Chang et al, 2010 ; Abboud et al, 2021 ).…”
Section: Pain Modelsmentioning
confidence: 99%